Effect of supplemental protein:energy ratio on the intake, digestibility, fill, and turnover of dormant bluestem range-grasses - T. DelCurto; R.C. Cochran; K.A. Jacques; D.L. Harmon; G. Towne; T.B. Avery; E.S. Vanzant (Kansas Agricultural Experiment Station Research Reports, 1987)
Feeding a low crude protein (12%) supplement depressed dormant bluestem range-grass fiber digestibility, whereas moderate (27%) and high (41 %) protein supplementation maintained forage digestibility and encouraged intake. Increased intake for moderate and high protein groups appeared to be associated with increased rumen dry matter and indigestible fiber fill.
Keywords: Cattlemen' s Day; 1987; Kansas Agricultural Experiment Station contribution; no. 87-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 514; Beef; Protein:Energy ratio; Intake; Digestibility; Fill; Bluestem